Numerical investigation of mesoscale multiphase mass transport mechanism in fibrous porous media - Zhe Li; Chengyan Wang; Lin Li; Jiafeng Wu; Zichao Yin; Dapeng Tan (Engineering Applications of Computational Fluid Mechanics)
At present, the proton exchange membrane fuel cell (PEMFC) is one of the most promising new energy solutions. The structure and material properties of the gas diffusion layer (GDL) are important factors that restrict the efficient water management and structural stability of PEMFCs. The complex mesoscopic fibrous porous structure of the GDL results in complex multiphase flow dynamics problems that have highly nonlinear characteristics. It is difficult to describe the details of mesoscopic multiphase coupled transport dynamics and numerically solve problems in which there is a two-phase flow with a high-density ratio. To solve these problems, a mesoscopic multiphase coupled transport model based on a lattice Boltzmann method and volume-of-fluid (LBM-VOF) model is proposed. Moreover, we also discuss the mechanism of the interaction between the fibrous porous structure and internal multiphase flow. The results obtained illustrate that the proposed method can obtain dynamic details of the flow field for fibrous porous media. The surface wettability of fibres strongly influences both the distribution and stability of liquid water clusters within porous materials. Concurrently, the fibre diameter assumes a pivotal role in governing lateral water diffusion and exclusion efficiency. This work lays a foundation for efficient water and thermal management of PEMFCs.